Electricity and electronics for renewable energy technology an introduction - Hemami, A. (Taylor & Francis, 2016)
Electricity and Electronics for Renewable Energy Technology: An Introduction provides a foundational understanding of electricity and the methods and devices specific to electricity from renewable sources. The book begins with a brief explanation of the necessary mathematics and then: Addresses the basics of electricity and relationships, motors and generators, transformers, and networks and distribution, Tackles the key concepts associated with electronics, diodes and transistors, switching devices, and power converters, Covers digital electronics from number systems and logic circuits to encoders and decoders, Explores advanced subjects such as reactive power and the operation of a transistor. A PowerPoint presentation are available with qualifying course adoption. Featuring extensive review questions and practice problems at the end of each chapter, Electricity and Electronics for Renewable Energy Technology: An Introduction instills an essential knowledge of electricity and electronics required for work with renewable energy.